2013
DOI: 10.1371/journal.pone.0064260
|View full text |Cite
|
Sign up to set email alerts
|

Actionable Gene Expression-Based Patient Stratification for Molecular Targeted Therapy in Hepatocellular Carcinoma

Abstract: BackgroundThe effectiveness of molecular targeted agents is modest in hepatocellular carcinoma (HCC). Efficacy of molecular targeted therapies has been better in cancer patients with high expression of actionable molecules defined as cognate target molecules. However, patient stratification based on the actionable molecules dictating the effectiveness of targeted drugs has remained understudied in HCC.Experimental Design & ResultsPaired tumor and non-tumoral tissues derived from a total of 130 HCC patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…However, 67% (37/55) of the HCC tumors with high tumor grades and 65% (15/23) of the tumors with an advanced clinical stage were negative for EGFR expression (Table ). This result is supported by the findings of Kwon et al ., who showed that downregulation of EGFR was found in advanced stage HCC tumors, as evaluated by the egfr mRNA expression in 130 HCC tumor and non‐tumoral samples . In addition, alcoholism, chronic HBV, and HCV infections were linked to the phosphorylation of EGFR in our study.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, 67% (37/55) of the HCC tumors with high tumor grades and 65% (15/23) of the tumors with an advanced clinical stage were negative for EGFR expression (Table ). This result is supported by the findings of Kwon et al ., who showed that downregulation of EGFR was found in advanced stage HCC tumors, as evaluated by the egfr mRNA expression in 130 HCC tumor and non‐tumoral samples . In addition, alcoholism, chronic HBV, and HCV infections were linked to the phosphorylation of EGFR in our study.…”
Section: Discussionsupporting
confidence: 58%
“…This result is supported by the findings of Kwon et al, who showed that downregulation of EGFR was found in advanced stage HCC tumors, as evaluated by the egfr mRNA expression in 130 HCC tumor and non-tumoral samples. 22 In addition, alcoholism, chronic HBV, and HCV infections were linked to the phosphorylation of EGFR in our study. The finding might provide new insight into the mechanism of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…In summary, greater liver toxicity associated with c‐Met inhibition may be anticipated in patients with more severe liver disease. The degree to which underlying disease might restrict the use of c‐Met inhibitors for the treatment of patients with HCC has yet to be established and may depend on additional factors including the subtype and grade of HCC, ethnicity, and hepatitis B and C virus infection …”
Section: Liver Disease and C‐met‐targeted Therapymentioning
confidence: 99%
“…Many hospitals use the Electronic Health Records system (EHRs) to integrate different kinds of medical data [1,2]. The data mining technology is widely applied on the EHRs to support clinical decision, including drug supervision [3], complication identification [4], disease prediction [5], patient stratification [6] and other related directions [7]. Among them, medical complication identification gets special attention.…”
Section: Introductionmentioning
confidence: 99%